PANCASILA AS A SOURCE OF LAW - Davina Cheysia Syafira; Habibi Farrelino; Nazhifa Zhafira Zea; Risky Fazar Ramadhani; Sabarina Tahlita Aisyah (Academic Solution Publisher, 2024)
This study aims to analyze the influence of understanding Pancasila as the foundation of the Indonesian state not only functions as a political philosophy, but also as a source of law that guides national and state life. The 5th principle of Pancasila,